Practical Real Estate Law, 8th Edition - Daniel F. Hinkel (Cengage Learning, 2020)
Learn the role of today's real estate paralegal as you examine the intricacies of real estate law and transactions in Hinkel's PRACTICAL REAL ESTATE LAW, 8E. Ideal for studying real estate practice and as an on-the-job reference, this comprehensive resource clearly explains the complexities of contemporary real estate law and legal principles using practical applications, case examples and the latest real estate legal forms. Updates detail the latest rulings and industry regulations, while case summaries illustrate legal principles in action. New case problems and assignments provide practice in reading and analyzing material. Meaningful discussions, checklists and illustrated forms guide you through real estate practice while emphasizing ethics. You examine all areas of transactional real estate--from contracts and brokerage relationships to surveys, title insurance, taxation and real estate finance related to residential and commercial processes in the United States.